Coronary Artery Disease Severity has a Strong Association with Epicardial Adipose Tissue Thickness - Sadaf Shaheen, Rosheena Nabeel Khan, Abdul Rehman, Iffat Raza, Sadaf Fatima, Sahrish Mukhtar (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Measure the EAT thickness by echocardiography in CAD patients and to compare it with healthy adults of Karachi population. Study Design and setting: It is a case control study. The study was carried out in the radiology (Echocardiography) Department of Ziauddin University Hospital Clifton Campus, Karachi. Methodology: In this study, there were315 participants among them there were159 cases of coronary artery disease and 156 healthy adults. The participants were selected through non probability convenience sampling technique. After filling the proforma including basic information the echocardiography for EAT thickness calculation was done. The data was analyzed on SPSS version 20. Numerical variables were used to derive means and standard deviations while ANOVA was applied to determine the worth along with coronary artery disease and healthy groups. P- Value less than 0.05 was considered as significant. Results: EAT mean thickness was found to be 15.45 ± 7.16 mm. Coronary artery disease group had drastically elevated EAT 16.77 ±9.80 mm in contrast to healthy adults group 14.13 ± 4.52 mm (p=0.02). Three vessel disease group had highest EAT thickness value of 18.79mm while one vessel disease group had lowest Epicardial Adipose Tissue value of 13.55mm. A considerable variation (p=0.001) in EAT thickness and CAD severity was found. Conclusion: Coronary artery diseased CAD group had greater EAT thickness as compared to healthy individuals. Among the CAD patients, the EAT was highest in three vessel disease and was lower in one vessel disease. Keywords: Adipose tissue, Coronary artery disease, Echocardiography, Epicardial